Pengembangan Model Bungge Cord Training pada Cabang Olahraga Bolavoli - Rayfal Fahmi Paturohman; Deden Akbar Izzuddin; Habibi Hadi Wijaya (MAN Insan Cendekia Jambi, 2026)
This study aimed to develop a Bungee Cord Training exercise model and examine its feasibility and effectiveness in improving the jumping performance of volleyball athletes. The background of this research was based on the low vertical jump ability of athletes, which affected the effectiveness of smash and blocking techniques. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The research participants were volleyball athletes involved in the trial of the developed training model. Research instruments included expert validation sheets and a vertical jump test to measure athletes’ jumping performance before and after the intervention. Data were analyzed descriptively to assess product feasibility and compared to determine training effectiveness. The results indicated that the Bungee Cord Training model was considered feasible based on expert and coach evaluations. Furthermore, the implementation of the training model resulted in improved jumping performance. Therefore, Bungee Cord Training can be used as an innovative and applicable alternative physical training method in volleyball athlete development.